Medical Genetics - Peyton, Ellie (United States : c, 2021)
Epigenetics is the study that deals with the heritable phenotype changes which do not involve changes in DNA sequence. Epigenetics usually shows changes that affect the activity of gene and expression but are also used to describe any heritable phenotypic change. Epigenetics in medicine consists of the use of drugs and epigenome influencing techniques in order to treat medical conditions. Epigenetic mechanisms have three categories - DNA methylation, histone modifications and regulatory RNA. It influences many diseases like cancer, diabetes, mental illness and heart diseases. In such situation, medical epigenetics helps in influencing these pathways. This book brings forth some of the most innovative concepts and elucidates the unexplored aspects of epigenetics. The various advancements in epigenetics in medicine are glanced at and their applications as well as ramifications are looked at in detail. This book, with its detailed analyses and data, will prove immensely beneficial to professionals and students involved in this area at various levels.
Includes index.
Includes bibliographical references.
Keywords: Medical genetics; Human chromosomes; Human chromosome abnormalities